Pengaruh Efisiensi Operasional, Pertumbuhan Perusahaan dan Struktur Modal terhadap Profitabilitas pada Perusahaan Sektor Transportasi dan Logistik di Bursa Efek Indonesia - Daulay, Putri Abellia; Fitra, Halkadri (Universitas Negeri Padang, 2025)
This research examines the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange in relation to (1) operational efficiency, (2) company growth, and (3) capital structure. In addition, firm size was employed as a control variable. The research population includes all transportation and logistics companies registered on the Indonesia Stock Exchange, with 22 companies selected through purposive sampling based on the criteria of consistently publishing financial reports from 2019 to 2023, resulting in 71 observation data. Data were analyzed using multiple linear regression with IBM SPSS Statistics 25. The findings reveal that (1) operational efficiency has a significant positive effect on profitability, (2) company growth also significantly enhances profitability, while (3) capital structure shows no significant influence on profitability in transportation and logistics companies. This study adds to the body of empirical research on the factors that influence profitability in developing countries, specifically in the logistics and transportation industry in Indonesia. In order to enhance financial performance, managers should prioritize efficiency improvements and sustainable growth plans. Investors and policymakers may also use the findings as a guide for assessing the stability and future prospects of the industry.